ABCs of z/OS system programming Volume 10 - Salla, Alvaro; Oughton, Patrick (IBM redbooks, 2018)
The ABCs of IBM® z/OS® System Programming is an 13-volume collection that provides an introduction to the z/OS operating system and the hardware architecture. Whether you are a beginner or an experienced system programmer, the ABCs collection provides the information that you need to start your research into z/OS and related subjects. If you would like to become more familiar with z/OS in your current environment, or if you are evaluating platforms to consolidate your e-business applications, the ABCs collection will serve as a powerful technical tool. This IBM Redbooks® publication, Volume 10, provides an introduction to IBM z/Architecture®, IBM z14 processor design, IBM Z connectivity, LPAR concepts and Hardware Configuration Definition (HCD). The contents of all the volumes are as follows: Volume 1: Introduction to z/OS and storage concepts, TSO/E, ISPF, JCL, SDSF, and z/OS delivery and installation Volume 2: z/OS implementation and daily maintenance, defining subsystems, JES2 and JES3, LPA, LNKLST, authorized libraries, SMP/E, IBM Language Environment® Volume 3: Introduction to DFSMS, data set basics storage management hardware and software, catalogs, and DFSMStvs Volume 4: Communication Server, TCP/IP, and IBM VTAM® Volume 5: Base and IBM Parallel Sysplex®, System Logger, Resource Recovery Services (RRS), global resource serialization (GRS), z/OS system operations, automatic restart management (ARM), IBM Geographically Dispersed Parallel Sysplex™ (IBM GDPS®) Volume 6: Introduction to security, IBM RACF®, Digital certificates and PKI, Kerberos, cryptography and z990 integrated cryptography, zSeries firewall technologies, LDAP, and Enterprise Identity Mapping (EIM) Volume 7: Printing in a z/OS environment, Infoprint Server and Infoprint Central Volume 8: An introduction to z/OS problem diagnosis Volume 9: z/OS UNIX System Services Volume 10: Introduction to z/Architecture, z14 processor design, IBM Z connectivity, LPAR concepts, and HCD Volume 11: Capacity planning, performance management, WLM, IBM RMF™, and SMF Volume 12: WLM Volume 13: JES3, JES3 SDSF.